Spatial Mapping Based on The Settlement Carrying Capacity Value in Banjarmasin Utara Sub District, Indonesia - Hadi, Inu Kencana; Efendi, Muhammad; Kumalawati, Rosalina; Pamuja, Indra Agung; Riduan, M.; Ramadhani, M. Ilham (Master Program in Mechanical Engineering, Gunadarma University, 2025)
Land Capability Unit refers to the process of evaluating the suitability and performance of land for specific purpose. In this context, it involves the assessment of land to determine the carrying capacity for residential land in the North Banjarmasin Sub-district. There are many potentials that can be used as attractions for residents outside the city of Banjarmasin to the study area, such as trade and service activities, education, and even health, which can have an impact on increasing the population. The increase in population is directly proportional to the increase in the need for residential. This study aims to analyze the carrying capacity of residential land in North Banjarmasin Sub-district. The results of the study showed that all villages in the study area had a DDPm value > 1, which indicates that the carrying capacity of residential land is relatively high. This value is an indicator that the area has the capacity for residents to settle.